Pareto-optimal matching allocation mechanisms for boundedly rational agents - Sophie Bade (Max Planck Institute for Research on Collective Goods, 2010)
This article is concerned with the welfare properties of trade when the behavior of agents cannot be rationalized by preferences. I investigate this question in an environment of matching allocation problems. There are two reasons for doing so: firstly, the finiteness of such problems entails that the domain of the agents' choice behavior does not need to be restricted in any which way to obtain results on the welfare properties of trade. Secondly, some matching allocation mechanisms have been designed for non-market environments in which we would typically expect boundedly rational behavior. I find qualified support for the statements that all outcomes of trade are Pareto-optimal and all Pareto optima are reachable through trade. Contrary to the standard case, different trading mechanisms lead to different outcome sets when the agents' behavior is not rationalizable. These results remain valid when restricting attention to minimally irrational behavior.
Keywords: C78; D03; D60; 330; Bounded Rationality; House Allocation Problems; Fundamental Theorems of Welfare; Multiple Rationales; Allokation; Matching; Pareto-Optimum; Wohnstandort; Beschränkte Rationalität; Theorie